Wyniki 18-letniego doświadczenia proweniencyjnego z bukiem zwyczajnym (Fagus sylvatica L.) w Nadleśnictwie Łobez - Kowalkowski, Wojciech (Leśne Prace Badawcze, 2013)
The experimental area is located in the Węgorzyno Forest Sub-District, Łobez Forest District. 29 Polish provenances of beech from their natural range were growth in a completely randomized block design with four replications. In 2010, after the end of the growing season, measurements were carried out on the experimental plot, including: determination of the survival rate and the diameter at breast height, and height of trees. Moreover, the total basal area and the total volume were calculated. Using ANOVA, statistically significant differences between provenances were apparent for four of the five traits measured; all except diameter at breast height. Provenances characterized by high values for the analyzed traits were considered the best adapted to the habitat conditions in the experimental plot, while provenances reaching low values were considered unsuitable for use under the conditions similar to those at the trial site location.